Cognitive Offloading: Can ubimus technologies affect our musicality? - Costalonga, Leandro; Pimenta, Marcelo (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2019.10427, 2019)
An interaction design that lean towards musical traits based on and constrained by our cognitive and biological system could, not only provide a better user experience, but also minimize collateral effects of excessive use of such technology to make music. This paper presents and discuss innate abilities involved in musical activities that - in the authors´ viewpoint - could be considered in design guidelines to computer music technologies, especially those related to ubimus.